To Cycle or not to Cycle. The Application of an Extended Innovation Diffusion Model for Sustainable Mobility - Perez-Macias, Noemi; Medina-Molina, Cayetano; Coronado-Vaca, Maria (Transformations In Business & Economics, 2024)
The high levels of pollution in cities and their impact on the quality of life of their citizens make it necessary to investigate healthier and more sustainable modes of mobility. Among the measures applied to achieve more environmentally friendly behaviour, cycling appears to be a less polluting mode of transport. It is therefore important to identify the combination of conditions that would explain the use of urban bicycles and those that lead people not to use them, as well as the existence of causal mechanisms in these relationships. To this end, the Multi-Level Perspective (MLP) and Set Theoretic Multi-Method Research (SMMR) were applied to a sample of 90 cities worldwide. The results show how the combination of landscape and regime conditions explains both the use and non-use of cycling as an urban mode of transport. The existence of a causal mechanism explaining bicycle use in German cities is also identified.